Indirection argumentative et mythologie grecque dans l'essai d'Albert Camus - Zemni, Bahia (2025)
Albert Camus' essays are full of mythological references. The invocation of Greek mythology, in particular, calls into question: between the illustration of a thought and the argumentative support of a point of view, the essayistic text of Camus is strewn with multiple Greek mythological references. This cannot be fortuitous and prompts us to seek the reasons for a procedure applied to "modern" times and civilization. If one considers that the recourse to mythology is a kind of indirect expression, there is also reason to wonder about the scope of a direct speech. What efficiency (or inefficiency) can the two have in this case?